ANALISIS PENGARUH PROFITABILITAS, LIKUIDITAS, DAN STRUKTUR MODAL TERHADAP KETEPATAN WAKTU PENYAMPAIAN LAPORAN KEUANGAN (STUDI PADA PERUSAHAAN FARMASI YANG TER DAFTAR DI BURSA EFEK INDONESIA TAHUN 2010 – 2014) - DEWI, ROSMALA; Yunita, Devi Sinta (Program Studi Manajemen Fakultas Ekonomi Universitas Palembang, 2019)
This study aimed to determine the effect of profitability (ROA), Liquidity (CR), and Capital Structure (DER) against timeliness of financial statements submission (Study On Pharmaceutical Companies Listed in Indonesia Stock Exchange 2010-2014). The sample taken 8 samples from the financial statements annualy of Pharmaceutical Company listed on the Indonesia stock exchange in 2010-2014. The methode research used is logistic regression. The result of this research shows that profitability variabel amounted to 0,550, liquidity variable amounted tp 0,696 and the capital structure amounted to 0,380 > α means apartid of 3 variables don’t have a significant impact on the timeliness of the financial reports. While simutaneously of the probabilty value is 0,066 > 0,05 means that the simultan eously of 3 variables don’t have a significant impact on the timeliness of the financial reports. The value of the coefficient of determibation (R2) is 0,220 it means that the variables of probability (X1), liquidity (X2) and capital structure (X3)contributed to the timely of financial statements submission (Y) by 22%, while the rest of 88% influenced by other variables which are not inclueded in this research, such as oponions of publik accorentants, company size, public ownership, the reputation of KAP, the age of the company and extraordinory items